Diversity and local business structure in European urban contexts - Fabula, Szabolcs; Skovgaard NielsenRikke; Barberis, Eduardo; Boros, Lajos; Hedegaard WintherAnne; Kovács, Zoltán (Hungarian Geographical Bulletin, 2021)
This article investigates the interconnectedness between neighbourhood diversity and local business structures. For this purpose, interviews with residents and entrepreneurs were conducted in three European cities: Budapest, Copenhagen, and Milan. The results show that diversity in the economic structure of urban neighbourhoods is equally important with regards to residents’ quality of life, the image of the neighbourhood, and local social cohesion. Therefore, the main recommendation is that policy makers should act to preserve the diversity of local business structures, and that the concept of diversity itself should be understood in a broader sense, taking local peculiarities into account.